EBV and HHV-6 Circulating Subtypes in People Living with HIV in Burkina Faso, Impact on CD4 T cell count and HIV Viral Load - Traore, Lassina (Mediterr J Hematol Infect Dis, 2017)
Epstein Barr Virus (EBV) and Human Herpes Virus 6 (HHV-6) are responsible for severe diseases, particularly in immunocompromised persons. There is limited data of the infection of these opportunistic viruses in Burkina Faso. The purpose of this study was to characterize EBV and HHV-6 subtypes and to assess their impact on CD4 T cell count, HIV-1 viral load and antiretroviral treatment in people living with HIV-1. The study population consisted of 238 HIV-positive patients with information on the CD4 T cell count, HIV-1 viral load and HAART. Venous blood samples collected in EDTA tubes were used for EBV and HHV-6 Real Time PCR subtyping. An infection rate of 6.7% (16/238) and 7.1% (17/238) were found respectively for EBV and HHV-6 in the present study. Among EBV infections, similar prevalence was noted for both subtypes (3.9% (9/238) for EBV-1 vs 4.6% (11/238) for EBV-2) with 2.1% (5/238) of co-infection. HHV-6A infection represented 6.3% (15/238) of the study population against 5.0% (12/238) for HHV-6B. EBV-2 infection was significantly higher in patients with CD4 T cell count ≥ 500 compared to those with CD4 T cell count less than 500 cells (1.65% vs 8.56%, p = 0,011). The prevalence of EBV and HHV-6 infections was almost similar in HAART-naive and HAART-experienced patients. The present study provides information on the prevalence of EBV and HHV-6 subtypes in people living with HIV-1 in Burkina Faso. The study also suggests that HAART treatment has no effect on infection with these opportunistic viruses in people living with HIV-1.